Peran Wali Kelas Dalam Pengelolaan Kelas di Sekolah Dasar Negeri 24 Teluk Batu - Susanti, Eni; Wibowo, Deki; Lestari, Novika (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2025)
Abstract: The research objectives are (1) to describe the role of the third grade homeroom teacher in classroom management, (2) to describe the challenges faced by the third grade homeroom teacher in classroom management. The research questions, namely (1) what is the role of the third grade teacher in classroom management at 24 Teluk Batu Elementary School (2) what are the obstacles faced by the third grade teacher in classroom management at SDN 24 Teluk Batu. The research was carried out in class III of 24 Teluk Batu state elementary school, Tembawang Panjang Village, Nanga Pinoh District, Melawi Regency, for the 2021/2022 academic year. This study uses qualitative research through observation, interviews, and documentation. The subjects in this study were the principal and homeroom teacher of class III, and the object in this study was the role of the homeroom teacher in class management. Data collection techniques using interviews, observation and documentation. The instruments in this study were interview sheets, observation sheets and documentation. The results showed that; (1) the homeroom teacher is always active even though it is not maximal. But the homeroom teacher is still trying to achieve the goals of class management effectively and conducive, this can be seen from several roles that have been carried out by class III homerooms in class management including; First, making some creativity by making erasers from unused cloth, Second prioritizing student activity, Third making seating arrangements, Fourth using simple media in class (2) obstacles faced by third grade homeroom teachers in classroom management, namely First, there are still those who obey the rules that has been determined by the homeroom teacher, secondly the lack of facilities in learning, and thirdly the lack of the homeroom teacher and the principal to pay attention to various needs in the classroom. Keywords: Role of homeroom, Management, Class. Abstrak: Penelitian ini bertujuan untuk (1) Mendeskripsikan peran wali kelas III dalam pengelolaan kelas, (2) Mendeskripsikan kendala yang dihadapi oleh wali kelas III dalam pengelolaan kelas. Pertanyaan penelitian yaitu (1) Bagaimanakah peran wali kelas III dalam pengelolaan kelas di SDN 24 Teluk Batu (2) Apa sajakah kendala yang dihadapi wali kelas III dalam pengelolaan kelas di SDN 24 Teluk Batu. Penelitian dilaksanakan di kelas III SDN 24 Teluk Batu Desa Tembawang Panjang, Kecamatan Nanga Pinoh, Kabupaten Melawi Tahun Pelajaran 2021/2022. Penelitian ini menggunakan jenis penelitian kualitatif melalui observasi, wawancara, dan dokumentasi. Adapun Subjek dalam penelitian ini yaitu kepala sekolah dan wali kelas III, dan dengan objek dalam penelitian ini adalah peran wali kelas dalam pengelolaan kelas. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Instrumen dalam penelitian ini adalah lembar wawancara, lembar observasi dan dokumentasi. Hasil penelitian menunjukan bahwa; (1) Wali kelas sudah menjalankan perannya walaupun belum maksimal. Tetapi wali kelas tetap berusaha untuk mencapai tujuan dari pengelolaan kelas secara efektif dan kondusif, hal ini terlihat dari beberapa peran yang telah dilakukan oleh wali kelas III dalam pengelolaan kelas diantaranya; Pertama membuat beberapa kreatifitas membuat penghapus dari kain yang sudah tidak dipakai, Kedua mengutamakan keaktifan siswa, Ketiga melakukan pengaturan tempat duduk, Keempat menggunakan media seadanya di kelas (2) Kendala yang dihadapi oleh wali kelas III dalam pengelolaan kelas yaitu Pertama masih ada siswa yang tidak mematuhi aturan yang telah ditetapkan oleh wali kelas, Kedua kurangnya sarana dalam belajar, dan Ketiga kurangnya kerjasama antara wali kelas dan kepala sekolah untuk memperhatikan berbagai keperluan di kelas. Kata kunci: Peran wali kelas, Pengelolaan, Kelas.